Chosen - Dekker, Ted, 1962- (Dekker, Ted, 1962- Lost books, 2007)
As the land of the Forest Dwellers is increasingly decimated by the Horde, Thomas Hunter, supreme commander of the Forest Guard, choses four sixteen-year-old recruits for a special mission--to find the seven lost Books of History that have power over the past, present, and future.